Kualitas Air pada DAS Bugis dan DAS Wain di Kawasan Hutan Lindung Sungai Wain Balikpapan - Sri Sarminah; Dyna Raya Anugerah; Marlon Ivanhoe Aipassa; Agus din (Fakultas Kehutanan Universitas Mulawarman, 2020)
This study aims to determine the latest water quality conditions in terms of physical, chemical and biological properties in the DAS Bugis and DAS Wain. Analysis of water sample was conducted at the Water Quality Laboratory of the Department of Aquatic Resources and Fisheries and Marine Sciences, Mulawarman University, Samarinda. Data analysis refers to the Water Quality Standards based on East Kalimantan Regional Government Regulation No. 02/2011 about Management of Water Quality and Water Pollution Control. The results showed that the parameters of temperature, colour, TSS, TDS, BOD5, SO4 and NO3 were included in the Class I water quality standards that can be used as drinking water or for other consumption purposes. COD parameters (in the Right River Basin), DO and NH3 (in the River Basin) were included in Class II water quality standards, which can be used for water recreation infrastructure / facilities, freshwater fish farming, animal husbandry and plants irrigation. The pH parameters in the DAS Bugis were included in class IV water quality standards that can only be used to irrigate plants. Pollutant loads that contribute a lot to enter were agricultural and agricultural waste and domestic waste originating from community forest areas.